Dysregulated metabolism and behaviors by disrupting gut microbiota in prenatal and neonatal mice. (25th June 2021) - Han, Guofeng; Nishigawa, Takuma; Ikeda, Hiromi; Hamada, Mizuki; Yang, Hui; Maesono, Saori; Aso, Kenta; Jing, Ashley; Furuse, Mitsuhiro; Zhang, Rong
Abstract: The live microbiota ecosystem in the intestine plays a critical role in maintaining the normal physiological and psychological functions in both animals and human beings. However, the chronic effect of microbiota disturbances during prenatal and neonatal developing periods on animal's health remains less studied. In the current study, pregnant ICR mice were fed with an antibiotic diet (7‐g nebacitin [bacitracin‐neomycin sulphate 2:1]/kg standard diet) from day 14 of conception, and their offspring were provided with the same diet till the termination of the experiments. Dams treated with antibiotics showed increased body weight along with enlarged gut. Antibiotic‐treated offspring revealed decreased bodyweight, increased food, water, and sucrose intake. Administration of antibiotics affected corticosterone responsivity to acute 20 min restraint challenge in male pups. In behavior tests, female pups showed decreased movement in open field while male pups revealed decreased latency to open arms in elevated plus maze test and immobility time in tail suspension test. Together, these results suggested that early antibiotic exposure may impact on the food intake, body weight gain, and emotional behavior regulation in mice.